Intellectual activity as a basis of innovative activity - Уткіна, Галина Анатоліївна (Pedagogy of Higher and Secondary Education, 2015)
Utkina G. А. Intellectual activity as a basis of innovative activity. In the article the relationship between the human factor and production factor knowledge management, or between intellectual activity and innovation activity. The article defines three of the ordered components of the educational process and their interactions: power knowledge; power absorption of knowledge (student); playing practical knowledge. The origin of knowledge is knowledge synergistic organization.